Corporate governance practices of contributory pension scheme operators in Nigeria - Aliu, Olanrewaju Atanda; Alaudin, Ahmadasri; Abdul Hamid, Mohamad Ali (Universiti Putra Malaysia Press, 2019)
Unlike the previous defined benefit pension scheme in Nigeria, the current contributory pension scheme (CPS) is characterised by separation of ownership and management of pension fund. In view of agency problem this portends, the need to empirically examine corporate governance (CG) practices of operators is of importance for CPS survival. Thus, this study examines corporate governance practices of operators of CPS in management and custody of the CPS fund. Survey data from 212 managers and assistant managers of CPS operators were analysed using one-sample t-test and mixed ANOVA. The results showed significant practices of CG mechanisms in the form of board independence, director independence, board disclosure and audit committee effectiveness. Significant difference was found in practice of above CG mechanisms. However, there was no significant difference in GC practices among various types of CPS operators. Similarly, the interaction of CG mechanisms with CPS operator type was also found to be insignificant. Based on the results, good corporate governance practices in the management of CPS fund is evident. However, it is recommended that there is an urgent need to intensify regulatory role of the part of CPS regulator- National Pension Commission to ensure that operators are not lacking behind in practices of various mechanisms of CG.